Effects of salinity on intestinal flora composition of Penaeus vannamei. Issue 5 (March 2020) - Cui, Qingman; Zhan, Wenhao; Zhao, Ziyue; Yuan, Chunying
Abstract: Based on IonS5TMXL sequencing platform, the effects of salinity on intestinal flora composition of Penaeus vannamei were studied. The results showed that the total number of OTUs in intestinal tract of P. vannamei in groups 6‰, 18‰ and 30 was 99, the unique number of OTUs in group 6‰ was 18, the unique number of OTUs in group 18‰ was 110, and the unique number of OTUs in group 30‰ was 53. At phylum level, the dominant bacteria in intestinal tract of three groups shrimp were Proteobacteria, Bacteroides, Firmicutes, Cyanobacteria, Actinobacteria, Tenericutes and Fusobacteria. At genus level, the main predominant bacteria in intestinal tract of shrimps were Defluviimonas, Stenotrophomonas, Shinella, Acinetobacter, Ruegeria, Rhodobacter, Nautella, unidentified Cyanobacteria and Pseudoalteromonas, and the relative abundance of intestinal microflora in different salinity groups shrimp was quite different. Simpson, Chao l, ACE and PD total tree indices of shrimps in salinity 18‰ group were higher than those of shrimp in 6‰ and 30‰ groups, while Shannon index was lower than that of shrimp in salinity 30‰ group, indicating that diversity and richness of intestinal bacterial community in salinity 18‰ group were higher than those of shrimp in 6‰ and 30‰ group. The results laid a foundation for further study on the effects of salinity on growth and metabolism of P. vannamei.